PERAN KEPALA SEKOLAH DALAM PEMENUHAN STANDAR PROSES PEMBELAJARAN DI SMK PGRI 3 KOTA SERANG - Hamidah Gustianti; Anton Aulawi; E. Nita Prianti (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2023)
ABSTRACT In general, the problem of education in Indonesia lies in the low quality of basic education at every level, both at the elementary secondary level and at the higher education level. The efforts of the Government of the Republic of Indonesia through the Ministry of Education and Culture in improving the quality and relevance of education are manifested in the form of establishing policies on National Education Standards in accordance with the mandate of the Law on the National Education System. National Education Standards are the minimum criteria regarding the education system in Indonesia and the issuance of Government Regulation Number 13 of 2015 concerning National Education Standards, aims to improve the quality of education in Indonesia. This study aims to determine the role of the headmasterl in monitoring the evaluation of the teaching and learning process for meeting the standards of the learning process at SMK PGRI 3 Serang City. Implementation of the standard learning process at SMK 3 PGRI Serang City, the Headmaster has supervised, monitored and evaluated teachers and education staff at least once every 1 semester or 6 months, even every week to be precise on Monday morning before the start of learning a meeting is held with all teachers first or morning briefing to provide direction, coaching and motivation, this is also done as an evaluation in the future so that it becomes even better. And when the headmaster has carried out supervision, monitoring and evaluation, don't forget to also follow up for the next 3 months to see if there are still things that haven't been improved when the teacher supervision has not met the standards of the learning process. The level of compliance with the learning process standards at SMK 3 PGRI Serang City, what researchers can conclude is that the level of compliance with learning process standards at the school is only around 70%. This is due to several factors which, according to researchers, educators have not fully met the learning standards that should be met. To meet process standards, teachers need to carry out a more interactive, structured and scheduled learning process, by taking advantage of very rapid technological developments so that learning is not always focused on textbooks and also to make the learning process more creative, innovative and attractive.